George - Gino, Alex (Scholastic Inc., 2017)
"When people look at George, they think they see a boy. But she knows she's not a boy. She knows she's a girl. George thinks she'll have to keep this a secret forever. Then her teacher announces that their class play is going to be Charlotte's Web. George really, really, REALLY wants to play Charlotte. But the teacher says she can't even try out for the part . . . because she's a boy. With the help of her best friend, Kelly, George comes up with a plan. Not just so she can be Charlotte -- but so everyone can know who she is, once and for all"--provided by publisher.